Development of Mobile Application to Present 3D Interactive Animation for Supporting of Emotional and Friend Relationship with Early Childhood: Miracle of Heart - Chansri, Poramin; Makthaworn, siriprasert; Phira, Kitsana; Sutti, Tanyatorn; Sittiwa, Ekkawit (Journal of Applied Informatics and Technology, 2022)
The purpose of this project was to create an interactive model for emotional support and relationships between friends for early childhood children and develop their skill concerning friendship as 3D Animation "Miracle of Heart". Viewers can participate in the simulation via a mobile app created with the following programs: Blender was used to sculpt models, generate settings, and animations; Adobe Premier Pro CC was used to edit video; Adobe After Effects CC was used to make motion graphics; Adobe Photoshop CC was used to design apps with Adobe XD; and Kodular.io was used to develop mobile apps. Five specialists examined the product to assess its quality. The satisfaction assessment of the sample of 53 viewers indicated that the average quality assessment was at a very good level, and all of the assessments were in very good criteria. The mean ( ) is 4.85 and the standard deviation is 0.37.